Cross-cultural adaptation of the Work Disability Diagnosis Interview (WoDDI) for the Brazilian context Adaptación transcultural del Work Disability Diagnosis Interview (WoDDI) para el contexto brasileño Adaptação transcultural do Work Disability Diagnosis Interview (WoDDI) para o contexto brasileiro - Vivian Aline Mininel; Vanda Elisa Andres Felli; Patrick Loisel; Maria Helena Palucci Marziale (Universidade de São Paulo, 2012)
The Work Disability Diagnosis Interview (WoDDI) is a structured interview guide developed by the University of Sherbrooke, Canada to help clinicians detect the most important work-related disability predictors and to identify one or more causes of prolonged absenteeism. This methodological study aims for the cross-cultural adaptation of the WoDDI for the Brazilian context. The method followed international guidelines for studies of this kind, including the following steps: initial translation, synthesis of translations, back translation, evaluation by an expert committee and testing of the penultimate version. These steps allowed obtaining conceptual, semantic, idiomatic, experiential and operational equivalences, in addition to content validity. The results showed that the translated WoDDI is adapted to the Brazilian context and can be used after training. El Work Disability Diagnosis Interview (WoDDI) es una guía de entrevista estructurada desarrollada por la Universidad de Sherbrooke (Canadá), para ayudar a los profesionales de la salud a detectar los predictores de mayor importancia para personas con trastornos relacionados con el trabajo y para identificar una o más causas de ausentismo prolongado del trabajo. Este estudio metodológico se dirige a la adaptación transcultural (WoDDI) para el contexto brasileño. El método siguió las recomendaciones internacionales para este tipo de estudio, el que comprende las siguientes etapas: traducción inicial, síntesis de las traducciones, retraducción, revisión del comité de expertos y prueba de la versión pre-final. Estas medidas permitieron obtener la equivalencia conceptual, semántica, idiomática y la experiencia operacional, además de la validación del contenido. Los resultados mostraron que el WoDDI traducido se adapta a la realidad brasileña e puede ser utilizado, después de la capacitación previa. O Work Disability Diagnosis Interview (WoDDI) é um guia de entrevista estruturada, desenvolvido pela Universidade de Sherbrooke (Canadá), para ajudar os profissionais de saúde a detectarem os fatores preditivos de maior importância para incapacidades relacionadas ao trabalho, e a identificarem uma ou mais causas de absenteísmo prolongado do trabalho. Este estudo metodológico objetivou a adaptação transcultural do WoDDI para o contexto brasileiro. O método obedeceu às recomendações internacionais para esse tipo de estudo, contemplando as seguintes fases: tradução inicial, síntese das traduções, retrotradução, avaliação por comitê de especialistas e teste da versão pré-final. Tais etapas permitiram o alcance das equivalências conceitual, semântica, idiomática, experiencial e operacional, além da validação de conteúdo. Os resultados demonstraram que o WoDDI traduzido está adaptado para a realidade brasileira e pode ser utilizado após treinamento prévio.